Deal breaker [compact disc, unabridged] - Coben, Harlan, 1962- (Coben, Harlan, 1962- Myron Bolitar novel., 2006)
Sports agent Myron Bolitar is poised on the edge of the big-time. So is Christian Steele, a rookie quarterback and Myron's prized client. But when Christian gets a phone call from a former girlfriend, a woman who everyone, including the police, believes is dead, the deal starts to go sour. Suddenly Myron is plunged into a baffling mystery of sex and blackmail. Trying to unravel the truth about a family's tragedy, a woman's secret, and a man's lies, Myron is up against the dark side of his business - where image and talent make you rich, but the truth can get you killed.